Exosomes Derived from microRNA-27a-3p Overexpressing Mesenchymal Stem Cells Inhibit the Progression of Liver Cancer through Suppression of Golgi Membrane Protein 1 - Christian Cedric Bongolo; Erick Thokerunga; Qian Yan; Mohamed Bassirou Moukeila Yacouba; Chao Wang (Stem Cells International)
Hepatocellular carcinoma (HCC) remains a significant health burden to date. Its early diagnosis and treatment are complicated by the lack of early diagnosis markers and multidrug resistance. microRNA regulation of HCC oncogenes are among the new diagnostic and therapeutic strategies being explored, although the mode of delivery of a therapeutic dose of the miRNA remains a challenge. In this study, we explored the use of exosomes from umbilical mesenchymal stem cells transfected with miR-27a-3p to interact with the oncogene GOLM1 in HCC and inhibit HCC progression both in vitro and in vivo. We first determined and compared the expression levels of miR-27a-3p in blood, various cell lines and tissues of HCC and their corresponding normal controls. We then employed bioinformatics analysis to determine the gene target for miR-27a-3p in HCC and later transfected upregulated miR-27a-3p in mesenchymal stem cells, and treated HCC cells with exosomes extracted from the transfected stem cells. We then created mouse models of HCC using balbc/nude mice and equally treated them with exosomes from miR-27a-3p transfected stem cells. The results showed that miR-27a-3p is downregulated in blood, cell lines, and tissues of HCC patients compared to normal controls. Exosomes from the miR-27a-3p transfected mesenchymal stem cells prevented HCC cell proliferation, invasion, and metastasis both in vitro and in vivo. Upregulation of miR-27a-3p prevented HCC through interacting with and downregulating GOLM1 as its target oncogene. In conclusion, miR-27a-3p is a potential therapeutic target for HCC acting through GOLM1.